Towards Using the Critical Decision Method for Studying Visualisation-Based Decision-Making - Hermawati, Setia; Cibulski, Lena; Lawson, Glyn (2021)
Visualisations provide significant support for effective reasoning and decision-making processes. Its value mainly lies in its ability to turn raw data into actionable insights that lead to a decision. This requires appropriate visual representations that are designed with the decision-maker's way of reasoning in mind. Understanding the cognitive aspects underlying decision-making with visualisations is therefore crucial. Cognitive task analysis methods have been used to elicit expert knowledge in a variety of decision-making scenarios, with the Critical Decision Method (CDM) focusing on the cognitive bases in naturalistic non-routine incidents. In this study, we aim to determine the feasibility of CDM for capturing the expert knowledge, strategies, and cues involved with visualisation-based decision-making processes. Based on an analysis of four semi-structured interviews, we evaluate the method's potential to inform the role of visualisation for human decision-making. We anticipate that our reflections on methodological insights can serve as a starting point for other human factors and visualisation researchers, who aim at studying strategies for higher-level decision-making and problem-solving tasks.
Keywords: Critical decision method; cognitive task analysis; interactive visualisation; decision-making